EFEKTIVITAS BEBERAPA JENIS PUPUK KANDANG FERMENTASI TRICHODERMA SPP. DAN MIKRO ORGANISME LOKAL (MOL) BONGGOL PISANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (ARACHIS HYPOGAEA L.) - WAWAN APZANI; SITI ZAINAB; BAHARUDDIN BAHARUDDIN; BAIQ AZIZAH HARYANTINI; I MADE SUNANTRA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the effect of several types of manure with Trichoderma spp. fungal fermentation, the effect of local micro-organisms (MOL) on banana weevils and the interaction of these two factors on the growth and yield of peanut plants. This study used an experimental method with field experiments conducted in Pancoran Hamlet, Banyu Urip Village, Gerung District, West Lombok Regency. This research was conducted from January to March 2023. The design used was a randomized block design (RBD) with factorial experiments. The first factor is the Local Micro Organisms (MOL) of banana weevil with 2 levels, namely M0 (without MOL) and M1 (Using MOL). The second factor was several types of manure with 4 levels, namely P0 (without fertilizer), P1 (chicken manure), P2 (cow manure) and P3 (goat manure). observation parameters. The treatment of several types of manure had a significant effect on the parameters of plant height at 4MST, 5MST and 6MST, the parameters of the number of leaves, the number of pods, the weight of the wet pods, the weight of the dry pods and the weight of the seeds planted. However, there is no interaction between the two factors. Treatment of goat manure (P3) Gives the highest yield on the parameter of seed weight planting up to 41.86 g/plant.